A large‐scale molecular phylogeny of flesh flies (Diptera: Sarcophagidae). (17th June 2014) - PIWCZYŃSKI, MARCIN; SZPILA, KRZYSZTOF; GRZYWACZ, ANDRZEJ; PAPE, THOMAS
Abstract The available data for Sarcophagidae in GenBank were analysed in order to reconstruct the most comprehensive phylogeny to date. GenBank was explored for nine markers that are commonly used in various molecular and phylogenetic studies of flesh flies. We obtained data for 187 species and constructed an aligned dataset with 9241 characters. However, the matrix suffered from 74% missing data due to a low number of sequences for some markers and in most of the cases only short fragments of the analysed genes were available. The reconstructed tree was taxonomically biased towards the subfamilies Paramacronychiinae (12% of the described species) and Sarcophaginae (8.6% of the described species) and specifically the genus Sarcophaga. The third subfamily Miltogramminae was represented by only 0.7% of described species. Moreover, about half of the included species were of forensic importance, while the percentage of such species in the entire family was estimated at 7%. Many nodes had very low support, so in order to increase the support and thereby identify a 'core topology', we pruned 'rogue' taxa and applied different substitution models. Both strategies improved support considerably, although some nodes still were left unresolved. An analysis of the distribution of bootstrap values across chronograms showed that the weakest phylogenetic signal is restricted to that part of the tree which coincides with the onset of rapid radiations mainly within the genus Sarcophaga. Our study is concordant with phylogenies obtained by other authors, with the most noteworthy exception being the subfamily Paramacronychiinae emerging as paraphyletic with regard to the Miltogramminae, which is in strong conflict with morphological evidence. We discuss the new findings in the light of traditional taxonomical classifications of Sarcophagidae and recent molecular studies.